Nanostructured Diamond-Like Carbon Films Grown by Off-Axis Pulsed Laser Deposition. (24th November 2015) - Yap, Seong Shan; Nee, Chen Hon; Yap, Seong Ling; Tou, Teck Yong
Abstract : Nanostructured diamond-like carbon (DLC) films instead of the ultrasmooth film were obtained by pulsed laser ablation of pyrolytic graphite. Deposition was performed at room temperature in vacuum with substrates placed at off-axis position. The configuration utilized high density plasma plume arriving at low effective angle for the formation of nanostructured DLC. Nanostructures with maximum size of 50 nm were deposited as compared to the ultrasmooth DLC films obtained in a conventional deposition. The Raman spectra of the films confirmed that the films were diamond-like/amorphous in nature. Although grown at an angle, ion energy of >35 eV was obtained at the off-axis position. This was proposed to be responsible for subplantation growth of sp 3 hybridized carbon. The condensation of energetic clusters and oblique angle deposition correspondingly gave rise to the formation of nanostructured DLC in this study.